Pengaruh Stres Kerja dan Dukungan Organisasi terhadap Kinerja Karyawan Bank Pembangunan Daerah Jambi Cabang Sengeti - Aqil Rajmico; Adria Wuri Lastari; Mulia Inda Purwati (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to examine the effect of job stress and organizational support on employee performance at Bank Pembangunan Daerah Jambi, Sengeti Branch. This research uses a quantitative method with a survey approach. The population in this study consisted of all employees of Bank Pembangunan Daerah Jambi Sengeti Branch totaling 33 employees. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using multiple linear regression analysis preceded by instrument testing (validity and reliability) and classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The results show that job stress has a positive and significant effect on employee performance with a significance value of 0.009 (< 0.05). Organizational support also has a positive and significant effect on employee performance with a significance value of 0.003 (< 0.05). Simultaneously, job stress and organizational support significantly influence employee performance with a significance value of 0.024 (< 0.05). The coefficient of determination (R²) value of 0.821 indicates that 82.1% of the variation in employee performance can be explained by job stress and organizational support variables, while the remaining 17.9% is influenced by other variables outside this study.